Uji Aktivitas Penghambatan Xantin Oksidase Isolat 6,4'-Dihidroksi-4-Metoksibenzofenon-2-O-Β-D-Glukopiranosida (C20H22O10) Dari Mahkota Dewa (Phaleria Macrocarpa (Scheff.) Boerl) - Aprilita Rinayanti; Sri Teguh Rahayu; Resta Dwi Syachfitri (Universitas Indonesia, 2016)
Hyperuricemia is condition which increased uric acid levels. Hyperuricemia is major factor that developed gout. Gout is a disease that was caused by the accumulation of monosodium crystals on tissues. Mahkota dewa (Phaleria macrocarpa (Scheff.) Boerl) is indonesia medicine that has effect such as lowering blood pressure, glocose levels, and uric acid levels. One of the chemical constituents in this plant was benzophenon as 6,4'-dihydroxy-4-metoksi benzofenon-2-O-β-D-glukopiranosida (C20H22O10). The purpose of this study was to determine the activity of 6,4'-dihydroxy -4-metoksi benzofenon-2-O-β-D-glukopiranosida (C20H22O10) that can be inhibited xanthine oxidase .The results showed that isolates 6,4'-dihydroxy-4-metoksi benzofenon-2-O-β-D-glukopiranosida (C20H22O10) has inhibitory activity against xanthine oxidase as IC50 values 15.705 mg/mL. However, allopurinol has xanthine oxidase inhibitory activity higher than isolates with IC50 value 0.091 mg/mL. Lineweaver-Burk plot showed that isolates 6,4'-dihydroxy-4-metoksi benzofenon-2-O-β-D-glukopiranosida (C20H22O10) has a competitive inhibitory activity.